Peroxidase activity as an indicator of water stress in sweet pepper plants - Klar, Antonio Evaldo [UNESP]; Jadoski, Sidnei Osmar; Lima, Giusepina Pace Pereira [UNESP] (My University, 2006)
The purpose of the study was to evaluate the physiological and biochemical behavior of sweet pepper (Capsicum annuum L.) plants under different soil water availability conditions and the efficiency of the peroxidase (EC. 1.11. 1.7) activity as an indicator of water stress in plants. The experiment was carried out at the Faculdade de Ciências Agronômicas UNESP, Botucatu, SP. Sweet pepper plants were grown for 230 days after transplanting of seedlings and arranged in a completely randomized experimental design with 4 treatments, two irrigation managements (50 and 1500 kPa) and two soil surface managements (presence or absence of black polyethylene covering), and six replications. Physiological activities, such as stomatal transpiration and resistance to water vapor diffusion, were evaluated as well as biochemical activities, such as peroxidase activity and total soluble protein in foliar tissues. It was observed that soil water availability may lead to physiological and biochemical alterations in plants. Successive water stress cycles may promote the development of characteristics responsible for improving plant tolerance to periods of low water availability. The peroxidase enzyme activity showed to be an efficient indicator of water stress in sweet pepper plants.
Keywords: Capsicum annuum L.; Enzymatic activity; Soil moisture; Soluble protein; Vegetable physiology; Biochemistry; Enzyme kinetics; Moisture; Physiology; Plants (botany); Soils; Stresses; Transpiration; enzyme activity; herb; physiological response; phytochemistry; seedling; soil moisture; soil water; transplantation; water availability; water stress; Capsicum annuum; Capsicum annuum var. annuum